MEDIASI YUDISIAL KE DALAM SISTEM PERADILAN PERDATA DI INDONESIA - Adnantara, Kadek Prediandrika (Jurnal Ilmiah Raad Kertha, 2024)
Judicial mediation is an alternative method of dispute resolution that has been growing rapidly lately. Judicial mediation assigning judges as mediators has many advantages. The success of this mediation is expected to ease the task of the judge because with this mediation it means that the parties to the dispute have contributed to the implementation of the principle of fast, simple and low-cost justice. As for the background of the problem, how effective is the judicial mediation itself in the civil justice system and what are the obstacles during judicial mediation in civil courts. The purpose of writing this thesis is to find out the effectiveness of Judicial Mediation and the obstacles that occur in Civil Courts. 1 of 2002 concerning the Empowerment of Courts of First Instance to Implement Peaceful Institutions. Supreme Court Regulation (PERMA) Number 2 of 2003 concerning Mediation Procedures in Courts. PERMA Number 1 of 2008 concerning Mediation Procedures in Courts. PERMA Number 1 of 2016 concerning mediation procedures in court. The results of the study concluded that the effectiveness of the implementation of Judicial Mediation in Civil Courts is ineffective because of the small peace agreement in the implementation of mediation. This can be seen from the obstacles in reaching a peace agreement in the Judicial Mediation process in Civil Courts which are still low due to the fact that first the parties do not have good faith in mediation, the two mediator judges in court are still few, third the number of impartial advocates or lawyers to reconcile .